The impact of the COVID-19 pandemic on STI surveillance data: incidence drop or artefact? - Sentís, A; Prats-Uribe, A; López-Corbeto, E; Et al. (BioMed Central, 2021)
Background Before the COVID-19 pandemic, STI were increasing in Europe, Spain and Catalonia were not an exception. Catalonia has been one of the regions with the highest number of COVID-19 confirmed cases in Spain. The objective of this study was to estimate the magnitude of the decline, due to the COVID-19 pandemic, in the number of STI confirmed cases in Catalonia during the lockdown and de-escalation phases. Methods Interrupted time series analysis was performed to estimate the magnitude of decline in the number of STI reported confirmed cases in Catalonia since lockdown, from March 13th to August 1st 2020, compared to expected values estimated with historical data. Results We found that since the start of COVID-19 pandemic the number of STI reported cases was 51% less than expected, reaching an average of 56% during lockdown (50% and 45% during de-escalation and new normality) with a maximum decrease of 72% for chlamydia. Our results showed that fewer STI were reported in females, people living in more deprived areas, people with no previous STI episodes during the last three years and in the HIV negative. Conclusions The STI notification sharp decline was maintained almost five months since lockdown to the new normality, this fact can hardly be explained without significant underdiagnosis and underreporting. There is an urgent need to strengthen STI/HIV diagnostic programs and services, as well as surveillance, as the pandemic could be concealing the real size of the already described re-emergence of STI in most of the European countries.